Development of the Teen Oral Health‐Related Quality of Life Instrument. (12th October 2016) - Wright, Wanda G.; Spiro, Avron; Jones, Judith A.; Rich, Sharron E.; Garcia, Raul I.
Abstract: Objective: The aim of this study was to develop the Teen Oral Health‐Related Quality of Life instrument (TOQOL) and demonstrate its validity and reliability in a diverse sample of 13–18‐year‐old adolescents. Methods: A total of 363 adolescents aged 13–18 years participated in this cross sectional study. Oral screening examinations were conducted to collect oral health status data. Adolescents completed the TOQOL and a generic measure of health‐related quality of life, the PedsQL. The psychometric properties of the TOQOL were evaluated in terms of face, content, convergent, concurrent and discriminant validity in addition to internal reliability. Results: The 16‐item TOQOL covers five domains: Physical functioning, Role functioning, Social functioning, Oral problems, and Emotional functioning. The total scale and subscales showed satisfactory reliability with Cronbach alpha ranging from 0.75 to 0.92. TOQOL scores showed significant associations with perceived oral health status and the PedsQL (convergent validity) and discriminated well between adolescents with caries and adolescents who were caries free (discriminate validity). Conclusion: The TOQOL is a valid and reliable oral health‐related quality of life measurement that can be recommended for self‐report in adolescents aged 13‐18 years.